Accuracy of Transperineal Sonography and Distal Loopogram in Determining Distal Rectal Pouch-Perineal Distance and Fistula on Anorectal Malformation Post Colostomy Patients in Dr. Mohammad Hoesin General Hospital Palembang - Halomoan Sejahtera; Sindu Saksono; Uli Hanna Marsinta; Erial Bahar (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2020)
Background: Imperforated anus is a congenital abnormality which is better known as anorectal malformation. The incidence of anorectal malformations is 1 in 4000 to 5000 live births. The incidence of anorectal malformations in Europe varies from 1.14 to 5.96 per 10,000 people and can change each year.1-3 The surgical approach in the management of anorectal malformations depends on the classification of anorectal malformations based on low, intermediate and high location. The distal loopogram or distal colostrography / colostrogram examination is an examination that is very important to determine the location of the distal rectum before definitive repair, but this examination has the disadvantage of using contrast and x-ray radiation. One alternative radiological examination that can be used for faster initial management is sonographic.7 Methods: This study was a diagnostic test study to assess the diagnostic accuracy of the distal loopogram / colostrography examination and sonographic examination with the transperineal approachon post-colostomy Anorectal Malformations patients at Mohammad Hoesin Hospital, Palembang in August 2019-October 20120 or until the number of research samples is met. Results: There were 21 samples in this study, 11 (52.4%) samples were dominated by clinical appearance without fistula. On the results of ultrasound examination, the majority of samples of rectouretral fistulas were 7 (33.3%). Loopogram examination found the majority of samples without fistulas as many as 10 (47.6%) samples. On intraoperative examination, 7 (33.3%) samples were obtained for rectouretral fistulas. The result of pouch-perineum measurement on ultrasound examination was 1.15 ± 0.6 cm, loopogram was 0.7 ± 1.5 cm, intra-operasionem was 1.8 ± 1.6 cm. In this study, USG has a very high accuracy value with a sensitivity of 100% and a specificity of 93.8% while the Loopogram has a sensitivity of 100% and a specificity of 68.8%. Conclusion: Transperineal ultrasound has a very high accuracy value with a sensitivity of 100% and a specificity of 93.8% while the Loopogram has a sensitivity of 100% and a specificity of 68.8%. Although there is a significant difference between the distal rectum -perineal distance calculation with a difference of -0.38 ± 0.70 cm, these two methods are equally accurate in assessing the distal rectal pouch -perineal distance and the location of the fistula.